Methodology for Developing Students' Speech Skills in Russian Language Based on Educational Technologies (International Journal of Scientific Trends, 2024)
This article focuses on developing a methodology for enhancing students' speech skills in the Russian language using educational technologies. It examines modern approaches, including individualized learning, gamification, project-based learning, and the integration of digital platforms. The study aims to establish the theoretical foundations and practical implementation of a methodology designed to improve the quality of student preparation and develop their communicative competencies. The research employs theoretical analysis, qualitative and empirical methods, including interviews with teachers, observation of the learning process, and examination of foreign practices (Finland, Canada, Japan). Results indicate that the use of educational technologies such as Moodle, Kahoot, and Quizlet contributes to a 35% increase in student motivation, a 25% improvement in academic performance, and the development of communication skills through project activities. The article's conclusions emphasize that combining traditional teaching methods with educational technologies ensures a more interactive, personalized, and effective educational process. Recommendations include incorporating digital platforms and a project-based approach into curricula, as well as enhancing teachers' qualifications for working with innovative tools.